The Wall of The House As The Grammar of Diversity (Catolic and Islamic Communication Model In Ntaram) - Marselus Robot (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to find a communication model for people of different religions in Ntaram, Flores and East Nusa Tenggara. The Ntaram understand their world as a synthesis perpetuated by differences. The Ntaram use the walls of their house as a medium to express their religious identity. The theory that is relevant to analyzing forms of symbolic communication is the theory of symbolic interaction. The Symbolic Interaction Perspective sees the social structure that is formed precisely by interaction. The way they communicate sets them apart from the rest of the family. In the process of meaning, there is a mental activity that distinguishes the meaning of human action from the movement of animals. Interpretation activities become a bridge between stimulus and response. The method used is qualitative with an ethnographic communication strategy. In this case, the researcher's task is to try to interpret and understand the behavior patterns and forms of communication of members of a community. Data was collected through in-depth interviews with purposively determined key informants. Also through Focus Group Discussion (FG), and observation, especially to obtain data related to context. The research findings show that the wall is who they are. Every data of the sili mai wae house that is visible on the living room wall is affixed with some holy images (such as Sufis or Islamic priests) of the world or calendars with Islamic overtones. As for ata le mai tana golo, identity is placed in the corner of the living room.